The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.2337/cd18-0017
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Around-the-Clock Clinical Pharmacy Specialists Into the Critical Care Team Can Increase Safety of Hyperglycemic Crisis Management

Abstract: IN BRIEF “Quality Improvement Success Stories” are published by the American Diabetes Association in collaboration with the American College of Physicians, Inc., and the National Diabetes Education Program. This series is intended to highlight best practices and strategies from programs and clinics that have successfully improved the quality of care for people with diabetes or related conditions. Each article in the series is reviewed and follows a standard format developed by the editors of Clinical Diabetes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…For example, CPSs on nighttime shifts are well positioned to improve the management of sedation 19,20 . In our institution, we found that the around‐the‐clock CPS staffing model helped improve management of patients with hyperglycemic crises 21 . Furthermore, a beneficial, collaborative prescribing program for emergent anticoagulation reversal was possible to implement in our facility due to the around‐the‐clock CPS staffing model 22 .…”
Section: Discussionmentioning
confidence: 87%
“…For example, CPSs on nighttime shifts are well positioned to improve the management of sedation 19,20 . In our institution, we found that the around‐the‐clock CPS staffing model helped improve management of patients with hyperglycemic crises 21 . Furthermore, a beneficial, collaborative prescribing program for emergent anticoagulation reversal was possible to implement in our facility due to the around‐the‐clock CPS staffing model 22 .…”
Section: Discussionmentioning
confidence: 87%